18F-FDG distribution pattern improves the diagnostic accuracy of single pulmonary solid nodule - Zhou, Nina; Zhang, Annan; Su, Hua; Zhao, Wei; Li, Nan; Yang, Zhi (Frontiers in Oncology, 2022)
Background The main purpose is to explore the use of visual assessment of the heterogeneous distribution of 18F-FDG in single pulmonary solid lesions to differentiate the benign from the malignant. Methods The 200 cases of pulmonary nodules or masses examined by 18F-FDG PET/CT were retrospectively analyzed. The heterogeneity of 18F-FDG distribution of the lesion was visually and quantitatively evaluated and the higher part of metabolism was observed and measured at the proximal or distal part to determine the lesion nature. The sensitivity, specificity, PPV, NPV, and accuracy of this method were calculated. Results Total 171 pulmonary lesions showed heterogeneity of 18F-FDG uptake, including the 111 malignant and 60 benign. 54/60 (90.00%) benign lesions showed higher 18F-FDG uptake visually at distal part, while 104/111 (93.69%) malignant lesions showed higher 18F-FDG uptake visually at the proximal part. This visual method has good repeatability with a high kappa value (0.821, p<0.001). 52/60 (86.67%) benign lesions showed higher 18F-FDG uptake quantitatively at distal part, while 107/111 (96.40%) malignant lesions showed higher 18F-FDG uptake quantitatively at the proximal part. The sensitivity, specificity, PPV, NPV and accuracy of visual and quantitative methods were 93.69%; 96.40%, 90.0%; 86.67%, 94.55%; 93.04%, 88.52%; 92.86%, 92.40%; 92.98%, respectively (p<0.001). When combining the metabolic value and morphological characteristics of PET/CT with visual18F-FDG heterogeneous features, the accuracy reached to 98.25%. The other 29 lesions (14.5%) with no heterogeneity were smaller (2.17 ± 1.06 vs 3.58 ± 1.48, P<0.001). Conclusions Benign and malignant lung lesions showed different heterogeneity of 18F-FDG uptake. Lung cancer can be effectively distinguished from infectious or inflammatory lesions by this simple and convenient method.